Urban children’s familiarity and feeling towards nearby nature - Mansor, Mazlina; Mansor, Mahani; Che Man, Shaibatul Islamiah; Ismail, Izzah Adibah (American Scientific Publishers, 2016)
Outdoor spaces within the neighbourhood areas are vital in supporting social systems of children. Children become comfortable, familiar and appreciative of their surrounding environment within their home proximity. The absence of conducive spaces, especially nearby nature for children to play and socialise can impact their psychological attitudes as they become adults. Playing in nearby natural surroundings in their neighborhood is found to reduce children’s stress and improve their physical functioning. This study explores children’s familiarity and use of nearby nature. It also reveals their feeling towards the natural environment in general. It gathered data from middle childhood children (n = 63) using interview survey designed in structured and semi-structured format. The study suggests that children in the neighbourhood of Kuala Lumpur city still have some degree of freedom to play outside and that they recognize the natural environment and regularly come in contact with it. Therefore, to nurture and encourage the activities, a children-friendly neighbourhood with good accessibility is vital to increase the children’s independent mobility. This study implies that the development of outdoor spaces for children in the neighbourhood areas should have more focus on sustainability and sensitivity towards social conditions of children.